Endophytic Beauveria bassiana in root, seed, and foliar-treated maize affecting on Spodoptera frugiperda larvae and its parasitization eggs - Herlinda, Siti; Saripudin, Saripudin; Thosin, Thosin; Madya, Sakha Prawira; Sari, Jelly Milinia Puspita; Suwandi, Suwandi; Anggraini, Erise; Suharjo, Radix (Universitas Lampung, 2026)
Spodoptera frugiperda is a highly polyphagous pest capable of causing up to 100% yield loss in maize. This study aimed to evaluate the effects of endophytic Beauveria bassiana applied through root drench, seed treatment, and foliar spray on the severity of larval feeding damage and egg parasitization by S. frugiperda. The B. bassiana isolate (JgSPK) used in this study was molecularly identified and deposited in GenBank (acc. no. MZ356494). Results indicated that among the three inoculation methods, seed treatment resulted in the highest endophytic colonization, followed by soil drench and foliar spray. Feeding on leaves colonized by the fungus increased larval mortality and resulted in abnormal pupation. Seed treatment showed the greatest potential in reducing larval feeding severity compared with foliar spray and soil drench applications. However, none of the inoculation methods significantly affected egg parasitization rates. Overall, endophytic B. bassiana reduced larval attack severity but did not influence egg parasitization, indicating compatibility with egg parasitoids. Further research is recommended to evaluate potential effects on larval parasitoids.